Pembangunan Aplikasi Augmented Reality untuk Pengenalan Benda di Museum Berbasis Android (Studi Kasus : Museum Blambangan Banyuwangi) - Yudha Akbar Pramana; Komang Candra Brata; Adam Hendra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Museum of Blambangan is one tourist attraction to add insight and knowledge in which there are objects of cultural heritage inside it. However as time goes by, there will be an ever-decreasing change of interest for students. This is influenced by the advance technology so they think that coming to the museum is boring. So in this thesis project, take the initiative to create an augmented reality application to introduce museum objects so it looks interesting. Because augmented reality is a technology that combines the real world and the virtual world, moreover augmented reality is one of the developing technology and is in great demand today. The development of this application uses a method adapted from the Agile SDLC model, which has 7 phases consisting of literature study, needs analysis, implementation, system testing, system deployment, and conclusions. The functionality testing is performed in accordance with the test cases on each functional requirement. The results of functionality testing show that the functional requirements have been met by the system. The result of usability testing by giving questionnaires of System Usability Scale (SUS) to the respondents of museum visitors and museum staf, obtaining visitor satisfaction result gets 86%. From these values can be concluded that this application can help the introduction of museum objects. Compatibility testing indicates that the work validity of these features can be well executed.